Impediments to exporting: A case study of australian manufacturing SMEs - Muhammad Mahmood (Journal of Accounting, Business and Management (JABM), 2005)
This study examines impediments to exporting faced by manufacturing small and medium enterprises (SMEs) in Australia using survey data. The results suggest that all factors identified as impediments to exporting have some bearing on exporting, but some factors feature more prominently than others as impediments. While a number of major impediments, such as the lack of export initiatives and competitiveness are very internal to SMEs, some other important ones such as tariffs and the lack of government assistance are external to them. SMEs, through productivity gains, innovation, networking, strategic alliances and improvements in management capabilities and appropriate training for staff, can help overcome many impediments that are internal to SMEs. Government policy initiatives can contribute to improve export performance of SMEs if they are directed to the areas of market access, export promotion and export facilitation